2021
DOI: 10.18857/jkpt.2021.33.2.76
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pilates Reformer Exercise on Standing Postural Alignment

Abstract: This study examined the effects of applying the Pilates reformer exercise to 17 adult women on the alignment of the standing posture. Methods: The subjects performed a Pilates reformer exercise for 60 minutes a day, three times a week, for a total of eight weeks. The Pilates reformer exercise consisted of five types: 1) lower and lift, 2) hundred, 3) plow, 4) airplane, and 5) twist. The standing posture alignment in the sagittal and frontal planes was measured using exbody 9100MOMI musculoskeletal analysis equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Furthermore, Kang and Park [11] reported that as a result of 8 weeks of performing Pilates by dance-majoring college students, the muscle mass of the extremities and the total muscle mass were significantly increased. In addition, performing regular reformer exercises for 8 weeks was reported to improve the sense of balance of the feet by reducing changes in the left, right, front, and back foot pressure and caused significant positive changes in the alignment of the frontal plane through stabilization of the lower back area and improvement of pelvic alignment by strengthening the abdominal and back muscles [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Kang and Park [11] reported that as a result of 8 weeks of performing Pilates by dance-majoring college students, the muscle mass of the extremities and the total muscle mass were significantly increased. In addition, performing regular reformer exercises for 8 weeks was reported to improve the sense of balance of the feet by reducing changes in the left, right, front, and back foot pressure and caused significant positive changes in the alignment of the frontal plane through stabilization of the lower back area and improvement of pelvic alignment by strengthening the abdominal and back muscles [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported the positive effect of Pilates exercises that emphasizes strength, stretching, and chest expansion with breathing techniques in postural correction through achieving spinal stabilization [9,12]. However, despite its frequent use in clinical practice in rehabilitation settings, clinical research on the link between Pilates and the enhancement of physical function in the field of physical therapy remains insufficient [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation